The Effect of Dividend Policy, Liquidity, Leverage on Company Value - Rahmadani, Alma Suci; Kusuma, Indra Cahya; Didi, Didi (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study aims to determine the effect of dividend policy as measured by DPR, liquidity as measured by CR, and leverage as measured by DER on profitability as measured by ROE and firm value as measured by Tobin's Q, as well as to determine the effect of dividend policy, liquidity, and leverage on firm value through profitability. The data used in this study were analyzed using multiple linear regression. The population of this study were food and beverage sub-sector companies listed on the IDX in 2018 to 2023. The research sample was selected using the purposive sampling method so that a total of 13 companies were obtained. The results of this study indicate that partially dividend policy and leverage affect profitability, while liquidity does not affect profitability. Profitability affects firm value while dividend policy, liquidity and leverage do not affect firm value. After being moderated by profitability, dividend policy and leverage have an effect on firm value while liquidity does not affect firm value. Simultaneously, dividend policy, liquidity and leverage affect profitability, and dividend policy, liquidity, leverage and profitability affect firm value.